Ambedkar’s Concept of Social Justice: It’s Relevance - Saikia, Rita (International Journal of Psychosocial Rehabilitation, 2020)
Ambedkar was a transparently honest challenging and eclectic liberal thinkers. He originates brainwave in the ideals of the French revolution and also in the socially forward looking and humanistic elements and values in Indian culture and civilization over the many decades ago. He campaigned against social discrimination against Dalits, along with this he was supporting the rights of Women and labor. Like Gandhi, B.R Ambedkar also believed that justice is all about liberty, equality and fraternity. Social justice has significance in the context of Indian society which is divided into Castes and Communities, and they create walls and barriers of exclusiveness on the basis of superiority and inferiority such inequalities pose serious threat to Indian democracy. The notion of social justice takes within its brush the objective of removing inequalities and affording equal opportunities to all citizens in social, economic and political affairs. Therefore, Ambedkar tried to solve the problems of Injustice through the constitutionalism. Here this paper deals with the concept of Ambedkar’s social justice and focus the relevance of it.